2012
DOI: 10.29074/ascls.25.2.102
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Helicobacter pylori Antibody in Different Age Groups in Central Texas

Abstract: The prevalence of exposure to the bacteria Helicobacter pylori in Central Texas is unknown. It has been shown that elderly individuals have a higher rate of infection than younger individuals. Exposure is even higher in the elderly living in long term care facilities. Evidence of exposure can be demonstrated by the presence of antibody to H. pylori. Plasma samples collected from several age groups are tested for the antibody to determine the exposure rate for different age groups. DESIGN: An exemption was gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
3
10
1
Order By: Relevance
“…In an existing cohort of Hispanic and NHW men, an overall H. pylori infection rate of 20% was identified, which was consistent with recent regional findings ( Patterson, Straten, & Jimenez, 2012 ). Sonnenberg et al (2010) reported that gastric biopsies from Texas residents had an overall infection rate of 12.7%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In an existing cohort of Hispanic and NHW men, an overall H. pylori infection rate of 20% was identified, which was consistent with recent regional findings ( Patterson, Straten, & Jimenez, 2012 ). Sonnenberg et al (2010) reported that gastric biopsies from Texas residents had an overall infection rate of 12.7%.…”
Section: Discussionsupporting
confidence: 89%
“… Sonnenberg et al (2010) reported that gastric biopsies from Texas residents had an overall infection rate of 12.7%. A study done in central Texas reported a prevalence of 24% in persons aged 41 to 60 years compared with other age groups ( Patterson et al, 2012 ), but results were not stratified by ethnicity. As expected, the infection rate among Hispanics was much higher than NHWs (30% vs. 9%), consistent with previous reports of national data ( Grad et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, analysis of waste pickers socio-demographic characteristics showed that seroprevalence of H. pylori was not only high among the youngest participants but also did not show a statistically significant increase with age. The former suggests an early exposure to H. pylori in waste pickers, and the latter is not consistent with the typical increase in the frequency of infection with age that has been reported in several studies [ 5 , 9 , 14 - 16 ]. Other putative socio-demographic factors associated with H. pylori infection, including low socioeconomic status [ 5 , 13 ] and low educational level [ 13 ], did not influence seroprevalence rates in waste pickers.…”
Section: Discussioncontrasting
confidence: 71%
“…Cross‐sectional seroprevalence studies place rates of current or past infection between 6%‐85% (Figure ; references:). Random‐effects regression models stratified by age showed the following overall seroprevalence estimates: for children <6 years of age 20% (95% CI: 14%‐25%); for children 6‐11 years old 37% (95% CI: 25%‐49%); for 12‐18 years old 44% (95% CI: 33%‐55%); and overall 33% (95% CI: 27%‐38%).…”
Section: Resultsmentioning
confidence: 99%